IMPLEMENTATION OF THE ELECTRONIC PROCUREMENT SERVICE PROGRAM (LPSE) IN SIDOARJO REGENCY - Natalia, Ineke Desi; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This research aims to analyze the implementation of the Electronic Procurement Service Program (LPSE) in Sidoarjo Regency as a form of e-Government application, focusing on supportive factors, institutional capacity, and the benefits generated in the governance of public goods/services procurement. Method: This research uses a qualitative descriptive approach with data collection techniques through field observations, interviews, and documentation in the environment of the Purchasing/Procurement Unit (UKPBJ) of Sidoarjo Regency. Informants were selected purposively, consisting of LPSE managers and members of the selection task force. Data analysis utilized the Miles and Huberman model with stages of data reduction, data presentation, and conclusion drawing. Result: The results of this study, based on Indrajit's theory of three success elements. First Support, LPSE in Sidoarjo Regency is backed by strong regulations and sufficient budget, reflecting the government’s commitment to digital procurement. Second Capacity, infrastructure and human resource readiness are relatively adequate, though some employees still face difficulties adapting to updated system features despite ongoing training. Third Value, LPSE enhances efficiency and transparency through a fully digital procurement process accessible via the official website, supported by the Community Satisfaction Survey (SKM) as a public feedback mechanism. Novelty: This study highlights the importance of strengthening adaptive capacity in the management of LPSE, especially in facing system changes and the decentralization of infrastructure management. Additionally, the integration of public feedback mechanisms through SKM is a unique finding that strengthens the role of community participation in the evaluation and improvement of digital procurement services at the local government level.